The political identity of south Lebanon from 1943 to 1978. (c2017) - Bassam, Abir (2017)
To understand the present political situation of the identity of South Lebanon, it is important to understand how this identity has developed since the formation of the Lebanese State. This thesis’s aim is to highlight a period of the history, from 1943 to 1978, during which the South of Lebanon was ignored by researchers. This small yet strategic place in area has played and is still playing an important role in conducting and contradicting the policy of the state of Lebanon, and sometimes the Middle East. This thesis has two major aims: one is to reveal the Southerner’s political identity before 1982 as well as to explain the different historical and social factors that led to this formation of identity. Secondly, to emphasize on the role of the different political parties in the South which have been marginalized in the studies in general, yet have played a role in forming the afore mentioned identity.